Efeito do treinamento funcional nas respostas psicofisiológicas na caminhada de idosas - Contieri, Magie Regina Ventura (2021)
The aging process is characterized by functional decline and physiological and biochemical changes. However, exercise when correctly prescribed is an efficient tool to prevent and reduce these functional losses. World Health Organization recommendations include 150 to 300 minutes of exercise per week at moderate intensity for health benefits. Researches that have already been carried out have sought to explain the effects of strength and aerobic training on walking speed, however, studies that analyzed psychophysiological variables in the same group before and after functional training are still scarce. Objective: To analyze the effect of 12 weeks of functional training on walking speed variables and psychophysiological responses between self-selected and prescribed conditions in elderly women. Methods: The study included 15 active elderly women, participants of an extension project at the Federal Technological University of Paraná, where functional training classes were offered to elderly women. Four experimental sessions of 20 minutes of walking were carried out, before and after 12 weeks of functional training, where, 1. Self-selected (AS), in which participants were instructed to walk at “preferred/selectedintensity”; 2. Prescribed – Easy Effort (EF); 3. Prescribed – Moderate Effort (ME) and 3. Prescribed – Difficult Effort (ED). The psychophysiological assessment (OMNI Scale of Subjective Effort Perception and affective valence – Sensation Scale) and heart rate (HR) were measured at the end of each walk, and the distance recorded to calculate the speed performed at each intensity. Data were described by mean and SD and inferential analysis was performed using two-way ANOVA with repeated measures (p<0.05). Results: The AS and EM intensity values did not show significant differences within the Walking speed (H: 1.44±0.02 and EM: 1.42±0.01 m/s) and PSE (H: 6, 21±0.12 and MS: 6.25±0.15). The affective valence remained stable and positive/pleasant regardless of the intensity of the exercise performed, showing no significant difference between the conditions (A: 4.81±0.09; EF: 4.81±0.06; ME: 4.78± 0.06; ED: 4.87±0.05). Walking speed showed a significant positive effect after training within the ED (pre 1.62±0.01; post 1.69±0.01). The subjective perception of exertion showed a progressive response according to speed and did not present significant differences between the AS AND EM intensity conditions (H: 6.21±0.12; EM: 6.25±0.15), however, the intensity of ED differed significantly in the time factor (pre: 8.5±0.12 and after 8.06±0.11), indicating lower perceived exertion with greater intensity indicated by heart rate. Conclusion: The elderly women had similar mean intensity values in AS and MS conditions, demonstrating a level of conditioning higher than the mean of the population of the same age group. Thus, 12 functional training sessions did not influence the AS, EF and EM walking speed results, however, the ED results showed positive differences, with an increase of 5,59% in speed and a reduction in the perceived exertion of 5,18% maintaining positive affect during exercise. Therefore, functional training is a beneficial strategy for promoting and maintaining the health of elderly women.